GLP-1 Receptor Agonist Effects on Lipid and Liver Profiles in Patients with Nonalcoholic Fatty Liver Disease: Systematic Review and Meta-Analysis. (12th November 2021) - Rezaei, Shahla; Tabrizi, Reza; Nowrouzi-Sohrabi, Peyman; Jalali, Mohammad; Atkin, Stephen L.; Al-Rasadi, Khalid; Jamialahmadi, Tannaz; Sahebkar, Amirhossein
Abstract : Aims . This meta-analysis of randomized placebo-controlled clinical trials assessed the effect of glucose-like peptide-1-receptor agonists (GLP-1RA) on the lipid profile and liver enzymes in patients with nonalcoholic fatty liver disease (NAFLD). Materials and Methods . Randomized placebo-controlled trials investigating GLP-1RA on the lipid profile and liver enzymes in patients with NAFLD were searched in PubMed-Medline, Scopus, Web of Science, and Google Scholar databases (from inception to January 2020). A random-effects model and a generic inverse variance method were used for quantitative data synthesis. Sensitivity analysis was conducted. Weighted random-effects meta-regression was performed on potential confounders on lipid profile and liver enzyme concentrations. Results . 12 studies were identified (12 GLP-1RA arms; 677 subjects) that showed treatment with GLP-1RA reduced alanine transaminase (ALT) concentrations (WMD = −10.14, 95%CI = [−15.84, −0.44], P < 0.001 ), gamma-glutamyl transferase (GGT) (WMD = −11.53, 95%CI = [−15.21, −7.85], P < 0.001 ), and alaline phosphatase (ALP) (WMD = −8.29, 95%CI = [−11.34, −5.24], P < 0.001 ). Aspartate aminotransferase (AST) (WMD = −2.95, 95% CI = [−7.26, 1.37], P = 0.18 ) was unchanged. GLP-1 therapy did not alter triglycerides (TC) (WMD = −7.07, 95%CI = [−17.51, 3.37], P = 0.18 ), total cholesterol (TC) (WMD = −1.17 (−5.25, 2.91), P = 0.57 ), high-density lipoprotein (HDL-C) (WMD = 0.97, 95%CI = [−1.63, 3.58], P = 0.46 ), or low-density lipoprotein (LDL-C) (WMD = −1.67, 95%CI = [−10.08, 6.74], P = 0.69 ) in comparison with controls. Conclusion . The results of this meta-analysis suggest that GLP-1RA treatment significantly reduces liver enzymes in patients with NAFLD, but the lipid profile is unaffected.